Particulars of Sports Terminology - Raximova Maloxat Alloberganovna (Research Parks Publishing LLC, 2022)
The article analyzes the scientific-theoretical foundations of sports terminology, the uniqueness of the field terminology, the stages of development, and the process of regulation of sports terms.